Biopharmaceutical aspects of drug formulation for neonatology: rational for indomethacin's complexation with hydroxypropyl-beta-cyclodextrin to treat patent ductus arteriosus (Revista Brasileira de Ciências Farmacêuticas, 2005)
Pharmacological therapy for newborns is faced on one hand, with an organism characterized by biological differences and functional immaturity with various grades of evolution for the same age, implying changes on the pharmacokinetic and pharmacodinamic medicine profiles. On the other hand, there is the effective need for pharmacotherapy. The "off label" use of medicines is therefore the only thing left to do, having in mind the risk of using therapeutic agents not studied for this special group of people. On this context it has been considered the use of cyclodextrin derivatives like hydroxypropyl-beta-cyclodextrin as an alternative to prepare oral formulations. With this review we intend to evaluate the rational for using indomethacin's complexation with hydroxypropyl-beta-cyclodextrin, to enhance bioavailability and reduce gastric toxicity characteristics, allowing its oral administration to treat patent ductus arteriosus on preterm and full-term newborns.